Sport Concussion Knowledge and Clinical Practices: A Survey of Doctors of Chiropractic With Sports Certification - Moreau, William J. (J Chiropr Med, 2015)
OBJECTIVE: The purpose of this study is to describe the knowledge base and clinical practices regarding concussion by sports-certified doctors of chiropractic. METHODS: A 21-item survey was distributed to the 312 attendees of the 2014 American Chiropractic Board of Sports Physicians Sports Sciences Symposium. Results were measured by frequency analysis and descriptive statistics for all surveys completed by sports-certified chiropractors. RESULTS: Seventy-six surveys were returned by sports-certified doctors of chiropractic. All (N = 76) 100% of respondents believe that the evaluation of concussion should be performed by a health care provider with training in concussion. The respondents actively assess and manage concussion in adults (96%), adolescents (95%), and children (75%). A majority (79%) of respondents believe that the Sideline Concussion Assessment Tool–3 represents a current standard of care for the sideline evaluation of the athlete who possibly has sustained a sport concussion. Most respondents agreed or strongly agreed that manual therapies may be appropriate in certain circumstances in adults (80%) and minors (80%). CONCLUSION: This cross section of certified sports chiropractors strongly believes that the evaluation of concussion should be performed by a health care provider with specific training in concussion. A high percentage of the sports-certified chiropractors who responded assess and manage sport concussion in their practice, and many of them endorse the use of the Sideline Concussion Assessment Tool–3 as a sideline assessment tool.